Implementation of smart technology to improve medication adherence in patients with cardiovascular disease: is it effective?. (1st February 2018) - Treskes, Roderick W.; Van der Velde, Enno T.; Schoones, Jan W.; Schalij, Martin J.
ABSTRACT: Introduction : Medication adherence is of key importance in the treatment of cardiovascular disease. Studies consistently show that a substantial proportion of patients is non-adherent. Areas covered : For this review, telemedicine solutions that can potentially improve medication adherence in patients with cardiovascular disease were reviewed. A total of 475 PubMed papers were reviewed, of which 74 were assessed. Expert commentary : Papers showed that evidence regarding telemedicine solutions is mostly conflictive. Simple SMS reminders might work for patients who do not take their medication because of forgetfulness. Educational interventions and coaching interventions, primarily delivered by telephone or via a web-based platform can be effective tools to enhance medication adherence. Finally, it should be noted that current developments in software engineering may dramatically change the way non-adherence is addressed in the nearby future.